SPEAKING PRACTICES IN AN ENGLISH CLUB: : STUDENTS’ VOICES IN PALEMBANG - Amrina Rosada; Renny Kurniasari; Winny Agustia Riznanda (Didascein : Journal of English Education, 2025)
This study aimed to investigate students’ perceptions of the speaking practices of the English Club at SMAN 19 Palembang, South Sumatra. One of the qualitative research designs, the case study, was applied. The purposive sampling technique was applied, involving 8 students who have been active in the English Club for more than a year. The data were collected through semi-structured interviews by using open-ended questions. Thematic analysis was then employed to analyze the data. The findings indicated that participating in the English Club: (1) enjoy fellowship and companionship, (2) receive moral and emotional support for their views, (3) challenged with reticence, (4) access to much more information, (5) get the same turn to speak, (6) more pleasant and provide more suitable material than regular class, (7) acquire new vocabularies and information, and (8) improved confidence. This study implied that English Clubs can create a supportive and student-centered environment that encourages authentic communication and reduces speaking anxiety, which is often lacking in traditional classrooms. By promoting social bonding and offering more engaging, relevant content, English Clubs foster both linguistic and affective development. This study contributes to the growing body of research on extracurricular language learning by highlighting how peer-supported, informal speaking practices can complement formal instruction. It also provides practical insights for educators and school administrators seeking to improve students' oral proficiency through meaningful, student-driven activities